38. THE UPPER CENTRAL INCISORS DIMENSIONS AMONG STUDENTS WITH ANTERIOR DIASTEMA IN HCMC UNIVERSITY OF MEDICINE AND PHARMACY (Vietnam Journal of Community Medicine, 2024)
Anterior diastema, which is a gap or space between two or more consecutive teeth, is a common aesthetic treatment problem of people seeking dentists. There are various factors contribute to the formation of anterior diastema, in which tooth size discrepancies being a key concern for clinical practitioners aiming to improve patient aesthetics. Our study aims to determine the dimensions and ratio of the upper central incisors among patients with anterior diastema, thereby helping clinicians choose appropriate treatments. This descriptive cross-sectional study was conducted on 2424 first-grade students in University of Medicine and Pharmacy HoChiMinh city. Intraoral scanning in both upper and lower jaws were made from 77 students who had anterior diastema using the Itero 5D Plus scanner. Tooth dimensions (width and height) of the upper central incisors were measured by using Ortho CAD™. All data are analyzed by SPSS 22.0 software. The incidence of maxillary midline diastema was 3,2%. The study showed that there are significant differences in the width and height of the upper central incisors between males and females (p
Keywords: Anterior diastema; Maxillary midline diastema; Tooth size discrepancies; Upper incisors dimensions; Itero 5D Plus scanner; Ortho CAD ™ software